2021
DOI: 10.1155/2021/4360122
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Use of Microsoft Kinect for Gait Abnormality and Postural Disorder Assessment

Abstract: Gait and posture studies have gained much prominence among researchers and have attracted the interest of clinicians. The ability to detect gait abnormality and posture disorder plays a crucial role in the diagnosis and treatment of some diseases. Microsoft Kinect is presented as a noninvasive sensor essential for medical diagnostic and therapeutic purposes. There are currently no relevant studies that attempt to summarise the existing literature on gait and posture abnormalities using Kinect technology. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…The studies focused specifically on measures to detect postural instability, shoulder position angulation and body joint angles, but the accuracy in the detection of posture disorders was not considered. 18 Another article evaluated the possibility to provide an accurate and automated assessment of axial postural abnormalities in PD patients by Kinect, evaluating the ICC between the angles calculated and the MDS‐UPDRS‐III 3.13 score. 19 These studies enrich the potential set of tools available for the early detection of axial postural abnormalities but do not consider the recent MDS consensus‐based criteria for their diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies focused specifically on measures to detect postural instability, shoulder position angulation and body joint angles, but the accuracy in the detection of posture disorders was not considered. 18 Another article evaluated the possibility to provide an accurate and automated assessment of axial postural abnormalities in PD patients by Kinect, evaluating the ICC between the angles calculated and the MDS‐UPDRS‐III 3.13 score. 19 These studies enrich the potential set of tools available for the early detection of axial postural abnormalities but do not consider the recent MDS consensus‐based criteria for their diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review reported 13 studies about postural disorder assessment with Microsoft Kinect, a motion‐sensing device for interaction with game consoles and computers. The studies focused specifically on measures to detect postural instability, shoulder position angulation and body joint angles, but the accuracy in the detection of posture disorders was not considered 18 . Another article evaluated the possibility to provide an accurate and automated assessment of axial postural abnormalities in PD patients by Kinect, evaluating the ICC between the angles calculated and the MDS‐UPDRS‐III 3.13 score 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The technological application of markerless motion capture during the gait analysis supports the validation in calculating body proportions (angles between body parts), timing, direction, and velocity without attaching markers to the skin. The main items of observation are; Posture, movement initiation and movement sequencing [46][47][48][49].…”
Section: Quality Of Lifementioning
confidence: 99%
“…[6][7][8] The common commercially available sensors used for markerless motion analysis are Leap Motion Controller (LMC; Leap Motion Inc., San Francisco, USA) and consecutive versions of Microsoft Kinect sensors (Kinect for Windows v. 1 (V1) and Kinect for Windows v. 2 (V2); Microsoft Corp., Redmond, USA). 9,10 For center-based and home rehabilitation purposes, Nintendo Wii Mote, Wii Balance Board (Nintendo Inc., Redmond, USA) and Microsoft Kinect motion-sensing game controllers have gained popularity over the past years. [11][12][13][14] Since Microsoft had released Azure Kinect Developer Kit (DK) in 2019, only a few studies were published concerning its usage.…”
Section: Introductionmentioning
confidence: 99%